2022
DOI: 10.1590/0103-8478cr20210209
|View full text |Cite
|
Sign up to set email alerts
|

Porcine circovirus 2 and 3 in wild boars in Southern Brazil

Abstract: Porcine circovirus 2 (PCV2) has a considerable economic impact on the pork industry worldwide for more than two decades. In 2016, a new circovirus, porcine circovirus 3 (PCV3), was described; since then, it has been reported to be associated with diseased or even in clinically healthy swine in several countries. Considering the importance of wild boars as reservoirs of swine pathogens and the extensive distribution of these animals in Rio Grande do Sul and throughout the national territory, we searched for PCV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…PCV3 has also been found in invertebrates, including ticks ( Ixodus ricinus ) in Italy and mosquitoes ( Aedes vexans , Anopheles sinensis , Culex tritaeniorhynchus , and Culex pipiens pallens ) in China ( 65 , 66 ). Records of PCV3 presence in wild boars are reported in Brazil ( 67 ). A study conducted by Franzo et al ( 49 ) in the Colli Euganei Regional Park of northern Italy collected 187 serum samples from wild boars and showed a high prevalence of PCV3, around 30%.…”
Section: Epidemiologymentioning
confidence: 99%
See 1 more Smart Citation
“…PCV3 has also been found in invertebrates, including ticks ( Ixodus ricinus ) in Italy and mosquitoes ( Aedes vexans , Anopheles sinensis , Culex tritaeniorhynchus , and Culex pipiens pallens ) in China ( 65 , 66 ). Records of PCV3 presence in wild boars are reported in Brazil ( 67 ). A study conducted by Franzo et al ( 49 ) in the Colli Euganei Regional Park of northern Italy collected 187 serum samples from wild boars and showed a high prevalence of PCV3, around 30%.…”
Section: Epidemiologymentioning
confidence: 99%
“…They analyzed serum samples from 85 sows with a history of reproductive disorders and 105 healthy sows, with a significantly higher PCV3 positive rate found in sows with reproductive failure (45.9%) than in healthy ones (21.9%) ( 57 ). In Brazil, a study conducted by Dal Santo et al ( 67 ) found that 270 out of 276 mummified fetuses tested positive for PCV3. Similarly, in Argentina, mummified and stillborn fetuses resulting from reproductive failures showed 100% positivity for PCV3 ( 44 ).…”
Section: Epidemiologymentioning
confidence: 99%
“… PCR/blood and ticks 5.97% blood samples and 50.54% ticks were positive southeastern Brazil [ 57 ] Ehrlichia spp. PCR/blood and ticks 9.24% of ticks were positive southeastern Brazil [ 57 ] Porcine circovirus 2 (PV2) and 3 (PV3) PCR/heart, kidneys, liver, lung, lymph nodes, spleen, and tonsils 15/26 (57.7%) positive for PV2 and PV3 southern Brazil [ 53 ] Porcine circovirus ELISA/serum 2/3 (67%) 2009/Colombia [ 49 ] Pneumocystis spp. Immunohistochemistry (IHQ)/skin, tonsils, spleen, lymph nodes, intestines, liver, stomach, kidneys, heart and the central nervous system 39/78 (50%) positive wild boars 16/78 (20.5%) wild boars coinfected by Pneumocystis and porcine circovirus type 2 2005–2008/Brazil [ 23 ] Torque teno Sus virus 1a (TTSuV1a) and and 1b (TTSuV1b) PCR/lymph nodes 43/80 (53.8%) positive for TTSuV1a, 5.0% (4/80) positive for TTSuV1b Histological analysis: Bronchopneumonia, vascular congestion, hemorrhage, edema, emphysema, fibrosis, follicular hyperplasia and presence of Metastrongylus sp.…”
Section: Impact On Native and Livestock Animal Healthmentioning
confidence: 99%
“…can lead to pneumonia, especially in young swine, and were detected in 50% wild boars of southern Brazil [ 23 ]. Porcine circovirus 2 and 3 virus are recognized to cause multiple disease conditions in swine and were detected in 57.7% wild boars from southern Brazil [ 53 ], and also detected in 67% animals in Colombia [ 49 ]. Also in Colombia, 67% wild boars were seropositive to vesicular stomatitis virus, considered endemic in South America [ 49 ].…”
Section: Impact On Native and Livestock Animal Healthmentioning
confidence: 99%